Novel BRAF gene fusions and activating point mutations in spindle cell sarcomas with histologic overlap with infantile fibrosarcoma - Penning, Alyssa J; Al-Ibraheemi, Alyaa; Michal, Michael; Larsen, Brandon T; Cho, Soo-Jin; Lockwood, Christina M; Paulson, Vera A; Liu, Yajuan J; Plank, Lukáš; Fritchie, Karen; Beadling, Carol; Neff, Tanaya L; et al. (Modern pathology, 2021)
Infantile fibrosarcoma (IFS)/cellular congenital mesoblastic nephroma (cCMN) commonly harbors the classic ETV6-NTRK3 translocation. However, there are recent reports of mesenchymal tumors with IFS-like morphology harboring fusions of other receptor tyrosine kinases or downstream effectors, including NTRK1/2/3, MET, RET, and RAF1 fusions as well as one prior series with BRAF fusions. Discovery of these additional molecular drivers contributes to a more integrated diagnostic approach and presents important targets for therapy. Here we report the clinicopathologic and molecular features of 14 BRAF-altered tumors, of which 5 had BRAF point mutations and 10 harbored one or more BRAF fusions. Of the BRAF fusion-positive tumors, one harbored two BRAF fusions (FOXN3-BRAF, TRIP11-BRAF) and another harbored three unique alternative splice variants of EPB41L2-BRAF. Tumors occurred in ten males and four females, aged from birth to 32 years (median 6 months). Twelve were soft tissue based; two were visceral including one located in the kidney (cCMN). All neoplasms demonstrated ovoid to short spindle cells most frequently arranged haphazardly or in intersecting fascicles, often with collagenized stroma and a chronic inflammatory infiltrate. No specific immunophenotype was observed; expression of CD34, S100, and SMA was variable. To date, this is the largest cohort of BRAF-altered spindle cell neoplasms with IFS-like morphology, including not only seven novel BRAF fusion partners but also the first description of oncogenic BRAF point mutations in these tumors.
Keywords: Sarcoma; kojenec; mladiství; plod; mužské pohlaví; Infant; Point Mutation; Adult; bodová mutace; onkogenní fúze; Infant, Newborn; Oncogene Fusion; ženské pohlaví; novorozenec; Humans; Proto-Oncogene Proteins B-raf; sarkom; protoonkogenní proteiny B-Raf; dospělí; Fetus; Female; Adolescent; lidé; Male